Recurrent Fever, Anemia, Arthralgia, and Genu Varum as Late Manifestations of Congenital Syphilis. Issue 8 (December 2015) - Quaresma, Liliana; Gonçalves, Juan; Estanqueiro, Paula; Salgado, Manuel
Abstract : Abstract: We report an unusual case of recurrent fever, inflammatory knee pain, genu varum, persistent anemia, and high erythrocyte sedimentation rate in a 28-month-old boy as late manifestations of congenital syphilis (CS). Despite standard penicillin treatment at the end of the first month of life, it recurred later in life, more than once. In the first relapse, manifested by a likely gumma lesion, the prior penicillin treatment plus a negative venereal disease research laboratory result unduly led to exclusion of CS. A second treatment with penicillin led to complete clinical resolution. Although rare, bow legs, recurrent fever, anemia, and inflammatory arthralgias may be manifestations of late CS. Congenital syphilis should be considered throughout early childhood, especially if history of syphilis infection is present. A negative venereal disease research laboratory result does not exclude late syphilis, present in nearly 30% of these patients. The possibility of atypical symptoms of this "great masquerader" should always be borne in mind.